2023
DOI: 10.1186/s12885-023-10788-4
|View full text |Cite
|
Sign up to set email alerts
|

KIF2C is a prognostic biomarker associated with immune cell infiltration in breast cancer

Abstract: Background The kinesin-13 family member 2C (KIF2C) is a versatile protein participating in many biological processes. KIF2C is frequently up-regulated in multiple types of cancer and is associated with cancer development. However, the role of KIF2C in immune cell infiltration of tumor microenvironment and immunotherapy in breast cancer remains unclear. Methods The expression of KIF2C was analyzed using Tumor Immune Estimation Resource (TIMER) datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…MAPK and JAK1/2 inhibitors, and STAT3 silencing, have led to S100A9 expression inhibition [44,46] but to our knowledge no direct link was yet established between Lapatinib and downregulation of S100A9 expression. The overexpression of KIF2C in many cancers has led to proliferation, EMT activation, invasion, and metastasis via PI3K/AKT, mTORC1, and MAPK/ERK signaling [47][48][49]. Due to its multifunctional role in cell cycle related processes and genomic stability, it was reported that the suppression of KIF2C inhibits mitosis [47].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MAPK and JAK1/2 inhibitors, and STAT3 silencing, have led to S100A9 expression inhibition [44,46] but to our knowledge no direct link was yet established between Lapatinib and downregulation of S100A9 expression. The overexpression of KIF2C in many cancers has led to proliferation, EMT activation, invasion, and metastasis via PI3K/AKT, mTORC1, and MAPK/ERK signaling [47][48][49]. Due to its multifunctional role in cell cycle related processes and genomic stability, it was reported that the suppression of KIF2C inhibits mitosis [47].…”
Section: Discussionmentioning
confidence: 99%
“…As such, investigating the behavior of infiltrating immune cells under Lapatinib treatment or Lapatinib/immunotherapy combinations could lead to new and more effective therapeutic applications of Lapatinib. Lastly, both S100A9 and KIF2C, as being an integral part of the tumor microenvironment, have been reported as suitable markers for evaluating immunotherapy response [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of breast cancer is a long-term process, and patients can develop drug resistance over time, making it challenging to improve long-term survival rates [ 17 ]. Previous studies on molecular research in breast cancer have made significant contributions to clinical diagnosis and prognosis [ 18 ]. The heterogeneity of breast cancer subtypes has also been explained through various genomic events including large-scale somatic calls [ 19 ].…”
Section: Introductionmentioning
confidence: 99%